Business Unit Strategy, Managerial Characteristics, and Business Unit Effectiveness at Strategy Implementation. - Gupta, A. K.; Govindarajan, V. (Academy of Management Journal, 1984)
Data from 58 strategic business units (SBUs) reveal that greater marketing/sales experience, greater willingness to take risk, and greater tolerance for ambiguity on the part of the SBU general manager contribute to effectiveness in the case of "build " SBUs but hamper it in the case of "harvest " SBUs. Despite the widespread acceptance of strategy's role in mediating an or-ganization's interaction with its environment (Andrews, 1971; Ansoff, 1965; Chandler, 1962; Child, 1972; Miles & Snow, 1978), the scope of research on strategy "implementation " has remained quite narrow. Following Chandler (1962), the concern has been predominantly with how a firm's organizational structure and control system are, or might be, related to the degree and nature of its product and geographic diversification (Fouraker